Differential Effects of Krill Oil and Fish Oil on the Hepatic Transcriptome in Mice - Burri, Lena; Berge, Kjetil; Wibrand, Karin; Berge, Rolf K.; Barger, Jamie L. (Frontiers in Genetics, 2011)
Dietary supplementation with ω-3 polyunsaturated fatty acids (ω-3 PUFAs), specifically the fatty acids docosahexaenoic acid (DHA; 22:6 ω-3) and eicosapentaenoic acid (EPA; 20:5 ω-3), is known to have beneficial health effects including improvements in glucose and lipid homeostasis and modulation of inflammation. To evaluate the efficacy of two different sources of ω-3 PUFAs, we performed gene expression profiling in the liver of mice fed diets supplemented with either fish oil or krill oil. We found that ω-3 PUFA supplements derived from a phospholipid krill fraction (krill oil) downregulated the activity of pathways involved in hepatic glucose production as well as lipid and cholesterol synthesis. The data also suggested that krill oil-supplementation increases the activity of the mitochondrial respiratory chain. Surprisingly, an equimolar dose of EPA and DHA derived from fish oil modulated fewer pathways than a krill oil-supplemented diet and did not modulate key metabolic pathways regulated by krill oil, including glucose metabolism, lipid metabolism and the mitochondrial respiratory chain. Moreover, fish oil upregulated the cholesterol synthesis pathway, which was the opposite effect of krill supplementation. Neither diet elicited changes in plasma levels of lipids, glucose or insulin, probably because the mice used in this study were young and were fed a low fat diet. Further studies of krill oil supplementation using animal models of metabolic disorders and/or diets with a higher level of fat may be required to observe these effects.